Inequality and growth in modern China - Wan, Guang Hua.; World Institute for Development Economics Research (Oxford : Oxford University Press, 2008)
This volume provides comprehensive, up-to-date coverage of inequality and poverty issues in China. Going beyond standard data sources and using state-of-art research techniques, it substantiates a number of findings and conclusions and ensures policy recommendations are reliable and robust.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Equality -- China; China -- Economic conditions -- 1949-